THE INFLUENCE OF EUPHEMISMS ON PUBLIC OPINION IN POLITICAL COMMUNICATION - Diyora Jalilovna Narimanova (The Conference Hub, 2025)
Euphemisms are linguistic tools that replace direct, often uncomfortable terms with softer expressions to address sensitive or controversial issues. In the realm of political discourse, euphemisms are employed strategically to guide public opinion, shift narratives, and evoke specific emotions. Politicians often use these linguistic devices to reframe policies and actions in ways that are more easily accepted by the public. This article examines the role of euphemisms in political communication, their effects on public perception, and the ethical challenges they present.
Keywords: euphemism, political discourse, public perception, emotional manipulation, political communication, rhetoric, framing.